COMPLEX APPROACH TO SELECTION OF TREATMENT OF ESOPHAGOGASTRIC HEMORRHAGE OF CHILDREN WITH PORTAL HYPERTENSION - A.A. Gafurov; V.V. Botvin'eva; G.U. Tuichiev; M.E. Abdullaeva (Union of pediatricians of Russia, 2008)
The researchers introduce the results of analysis of outcomes of operation in 38 children (7-15 years old) with liver cirrhosis and portal hypertension. The duration of the disease was from 2 to 12 years. recurrent 2-5 hemorrhages were hoted in 17 (44,7%) of the patients. the analysis of surgical interventions have shown that Tanner-Bairov`s operation was preferable among non bupassing and non traumatic operations.Key words: liver cirrhosis, portal hypertension, hemorrhage, conservative therapy, surgical correction, children.